Altitudinal distribution of the Muscidae, Calliphoridae and Sarcophagidae in Vietnam. Part 2: The species at altitude over 1200 m - Thinh, Ta Huy (Academia Journal of Biology, 2015)
During the petiod of 1995-2002, the author has collected 156 species of house flies, blow flies and flesh flies from 8 localities at altitudes of 1200-2500 m in Vietnam. Forty nine species are characteristic for this zone, of which 31 species are of house flies, 10 of blow flies, and 8 of flesh flies. Among them, 17 ones are of palaearctic or holarctic composition, they are Eudasyphora cyanicolor, Hydrotaea dentipes, H. meteorica, H. gandakiana, Limnophora setinerva, L. argentata, Phaonia mystica, P. kambaitiana, Muscina angustifrons, M. pascuorum, Polietes lardaria (Muscidae); Calliphora vomitoria, Aldrichina grahami, Melinda itoi, M. pusila, Stomorhina obsoleta (Calliphoridae); Bercaea haemorhoidalis (Sarcophagidae). It is interesting that these species have been found only in localities at altitudes over 1500 m of the Hoanglienson mountain. The present paper records 7 new species for Vietnam: Polietes lardaria (Fabr.), Lucilia bismarckensis Kurahashi, Isomyia pictifacies (Bigot), Melinda itoi Kano, Stomorhina obsoleta (Wd.),Bercaea haemorhoidalis (Fall.) at altitudes over 1200 m and Melinda crinitarsis Vill. at altitude of 1200 m.